Legislation driven scenarios based on recent construction advancements towards the achievement of nearly zero energy dwellings in the southern European country of Cyprus - Fokaides, Paris A.; Christoforou, Elias A.; Kalogirou, Soteris A. (My University, 2014)
Europe has a significant target ahead to fulfill: to achieve the goal of nearly zero energy buildings from the year 2021. This paper presents viable scenarios to achieve the achievement of nearly zero energy dwellings in the southern European country of Cyprus. The analysis is based on the documentation of the developments in the building sector after the adoption of mandatory building insulation regulations. For this purpose, data concerning the building stock of Cyprus before the adoption of the regulation of thermal insulation, as well as the construction characteristics for sixty dwellings which were built from 2010 to 2012 are compared. The ability of adoption of renewable energy in the building sector is also analyzed. Several scenarios are examined and a matrix defining the possible ranges of primary consumption of dwellings in Cyprus considered as nearly zero energy are presented. Possible scenarios examined in relation to consumption of dwellings in Cyprus by 2020 showed that this would range from 65 to -40kWh/m2 year, depending on the degree of renewable energy technologies penetration. The outcomes of this work are particularly revealing with regard to the definition of feasible consumption targets for nearly zero energy dwellings in southern Europe by 2020.
Keywords: Energy performance certification; Nearly zero energy buildings; Renewable energy technologies